Chlorophyll-a concentration in the Tajwid Lake, Langgam Sub-district, Pelalawan District, Riau Province - Situmorang, Libra Trio; Sihotang, Clemens; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Tajwid lake is an oxbow lake that receives water from the Kampar River during rainy season. To understand the concentration of chlorophyll-a in this lake, a research has been conducted in February 2016. The chlorophyll-a samples were collected from three statios namely station I (in let), station II (in the middle of lake) and station III (in the end of the lake). In each station, the water was sampled from the surface, in middle of water column and in the bottom of the lake. Sampling was done three times, once per week. Results shown that chlorophyll-a concentration in the surface was 13.52-15.75 μg/L, in the middle of water column was 8.18-10.85 μg/L, and in the bottom of the lake was 4.87-7.17 μg/L. Water quality results shown that transparency: 52-69 cm, depth: 6-12 m, temperature: 28-30 0C, pH: 5-6, DO: 2.3-8.3 mg/L, CO2: 4.9-13.9 mg/L, nitrate: 0.02-0.11 mg/L, phosphate: 0.02-0.10 mg/L, and phytoplankton abundance: 723-4,485 cells/L. The concentration of chlorophyll-a in Tajwid Lake indicate that the trophic status of the lake was mesotrophic, the water quality is good and it may be able to support the life of aquatic organisms.Keywords : Chlorophyll-a, mesotrophic, Tajwid Lake